A 225 kW Direct Driven PM Generator Adapted to a Vertical Axis Wind Turbine. (31st October 2011) - Eriksson, S.; Bernhoff, H.; Leijon, M.
Abstract : A unique direct driven permanent magnet synchronous generator has been designed and constructed. Results from simulations as well as from the first experimental tests are presented. The generator has been specifically designed to be directly driven by a vertical axis wind turbine and has an unusually low reactance. Generators for wind turbines with full variable speed should maintain a high efficiency for the whole operational regime. Furthermore, for this application, requirements are placed on high generator torque capability for the whole operational regime. These issues are elaborated in the paper and studied through simulations. It is shown that the generator fulfils the expectations. An electrical control can effectively substitute a mechanical pitch control. Furthermore, results from measurements of magnetic flux density in the airgap and no load voltage coincide with simulations. The electromagnetic simulations of the generator are performed by using an electromagnetic model solved in a finite element environment.